Six solutions for clinical study data sharing in Germany - Evgeny Bobrov; Christina Habermehl; Daniel Strech; Tracey Weissgerber; René Bernard (BMC Medical Research Methodology)
Abstract Sharing clinical study data is endorsed by many funders and journals, international policy frameworks, and patients. Reuse of clinical study data demonstrably improves health research, and emerging technologies may enhance the value derived from shared data. Unfortunately, clinical research has failed to harness the transformative power of data sharing, and sharing remains the exception. This opinion piece focuses on the massive obstacles to sharing clinical study data in Germany, which results in very low sharing rates, wasted resources, and frustration among local researchers and international partners. We argue that this sharing crisis demands immediate and concerted action. As a remedy, we propose six feasible steps to boost clinical study data availability in Germany, derived from our experience consulting researchers and exploring solutions with international partners. Our recommendations target ethics committees, trial registries, infrastructures, and governance, while addressing data protection concerns. These measures must be flanked by further actions to foster data sharing skills and knowledge as well as, most importantly, the provision of appropriate incentives. Nevertheless, the proposed changes would be a breakthrough for clinical study data sharing in Germany, removing barriers regarding infrastructures, awareness, legal uncertainty, and responsibilities.